A Review of Treatment Options in Paediatric Sleep-disordered Breathing - Yu-Shu Huang; Christian Guilleminault (Pediatric Respirology and Critical Care Medicine)
The clinical presentation of paediatric obstructive sleep apnoea (OSA) is different from that reported in adults. Children with paediatric OSA have more disturbed nocturnal sleep than excessive daytime sleepiness and present with more behavioural problems such as hyperactivity. They have sleep-related issues such as nocturnal enuresis and sleep-terrors and psychiatric problems such as depression and insomnia. Adenotonsillectomy has been the recommended treatment for paediatric OSA, but this practice as the initial treatment for all children has been questioned. The orthodontic approaches have been studied in children. Preliminary studies have suggested that rapid maxillary expansion and mandibular advancement with functional appliances may be effective even in children. Mandibular advancement devices, however, are not recommended for pre-pubertal children. These devices have been used in children in the late-teens, but long-term follow-up data are still lacking. Another non-invasive treatment is myofunctional therapy that has not been widely investigated. In syndromic children and where hypoventilation during sleep is present, positive airway pressure ventilation can be given. Nasal allergies are common in children. Increased nasal resistance impacts on breathing during sleep. Therefore, the treatment of nasal allergies with anti-inflammatory agents is an integral part of the management of paediatric OSA. Another important aspect of paediatric OSA is the presence of a short lingual frenulum and less frequently, a short nasal frenulum. They have been shown to cause abnormal growth of oral-facial region leading to OSA. Gastroesophageal reflux is both a cause and consequence of OSA and should be treated if present. The recent advance in the understanding of the pathogenesis of paediatric OSA lends hope that early recognition and management of factors that lead to the development of OSA may reduce the frequency of this disease and its sequelae. However, these factors are mostly unknown or ignored by specialists and general paediatricians during the early childhood orofacial development.